The efficiency of tourism sector in EU mediterranean coastal regions: The effects of seasonality and spatiality on demand - Spyros Niavis; Dimitris Kallioras (REGION, 2021)
The present paper studies the effects of seasonality and spatiality of tourist flows on the regional performance of tourism sector. The empirical analysis is conducted for 37 coastal North Mediterranean EU NUTS II regions, for the period 2010-2016, and is based on a triplet of quantitative indices and on a two-version regression model. The empirical analysis demonstrates that a typical linear function seems to be inappropriate to describe the relationships of these tourism features, as an N-shaped relationship between performance and seasonality and a U-shaped relationship for performance and spatiality were found.
Keywords: 330